Prevalence of smoking among national military service recruits in UAE - Almesmari, Sara; AlAmeri, Fayeza; Al Shanqaiti, Houd; Al Mansoori, Latifa; Heena, Humariya (Frontiers in Public Health, 2024)
Background: According to the various screening programs conducted, the prevalence of tobacco use among UAE Nationals is high. A considerable increase is also seen in various forms of smoking is seen among young military men during deployment which results in loss of physical health, less productivity, readiness and increased health care utilization. Also smokers are more likely to develop other addictions and chronic medical conditions.Aim: To estimate the prevalence of smoking among national military service recruits in the United Arab Emirates and to find its relation with various factors: sociodemographics, lifestyle, comorbidities, and military environment.Methods: A cross sectional study was conducted amongst national service recruits selected by random stratification through a self-administered anonymized questionnaire which was distributed to a final sample of 369 patients. Data was analyzed using SPSS version 16. Chi square, percentage and frequencies were used to present the data where applicable. A p value < 0.05 was considered to be significant.The prevalence of smoking among national military service recruits was 41.6%. As the level of education increased the prevalence of smoking decreased. Smokers with insufficient income, divorced or widowed recruits tend to smoke more as against single and married recruits. Smoking rates were decreased in those who exercise regularly. There was a significant relationship between smoking status and chronic diseases. Smoker gatherings inside military campus encouraged initiation of smoking or its continuity. About half of the smokers were not satisfied with environment at military facilities.Smoking has high prevalence among national service military recruits. For this reason, a goal directed future plan toward screening of smokers among recruits and assigning them to smoking cessation clinics and educational seminars prior to joining the national service is the need of the hour.